The pathological technical and tactical movements of a soccer player during return to sport predicts a second anterior cruciate ligament injury - D'Onofrio Rosario; Sannicandro Italo; Manzi Vincenzo; Annino Giuseppe; Bojan Bjelica; Nikola Aksovic (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2023)
Background: Return to sport after Anterior Cruciate Ligament (ACL) reconstruction remains a difficult decision-making process that is not structured on shared and homogeneous assessments. This greatly elevates the risk factors for second injuries. Objective: Highlight football-specific gestural, pathological, technical-tactical patterns that contribute to new ACL injuries (ipsilateral graft rupture or contralateral rupture of the native ACL). Material and method: For the purpose of this literature review, peer-reviewed and nonpeer-reviewed indexed journals were consulted from 1979 to the present. Studies were identified by searching them on PubMed/MEDLINE databases. The following search terms were used: "second ACL injury," "cutting maneuver and ACL", "sidestep cutting technique and ACL" "Valgus knee in sport" "change of direction and ACL injury" "pressing soccer" tackle in soccer". The literature search was directed, also, to the Gray Literature. Result: An immediate pressing or re-aggression on the adversary, tackle, or cutting maneuver is clinically read as moments of risk factors, injury, or re-injury, for both the ball bearer and the defender. We found how a good deal of literature emphasizes how side-to-side gestural asymmetries, during technical and tactical movements, present during return to sport can elevate risk factors for second ACL injuries. During ball recovery, 4 main game situations have been found to elevate the risk factors of knee capsular ligament injuries: (1) during tactical moments of collective pressing or individual pressure; (2) in the postural rebalancing phase after moments of instability following the kicking of the ball; (3) dysfunctional moments from gestural instability, in landing, after a header in single-pedal support; (4) during a tackle by direct contact or indirect contact on the joint. Conclusion: Residual pathological movement's side-to-side asymmetries and postural-dysfunctional pictures related to specific gestures after ACL reconstructive surgery are predictive factors of second ipsilateral ACL injury or injury to the contralateral limb. Given, however, the subjective interpretation of movement quality assessments, their relative reliability and validity in the diagnostic and therapeutic use of complex sports gestures, pressing, and cutting maneuvers, during the process of return to sport should be analyzed together and clinical assessments to identify other and consistent predictors of second ACL injuries.